Metodologia para estimativa de custos de cuidados com saúde: Análise dos fatores de gravidade e recomendaç\~oes para reduç\~ao dos custos - Ieda Maria de Oliveira Lima; Júlia Greve; Patrícia Alessandra Morita (Instituto de Pesquisa Econômica Aplicada (IPEA), 2008)
– The aim of this study was to evaluate the contributing factors to the severity of traffic accidents in Brazilian highways and to establish correlations between the severity of accidents and injuries with data regarding the victim, the accident, pre-hospital, hospital and post-hospital care, and road infrastructure, and to verify which of these factors contributed to the severity of injuries, by use of the database of 565 interviews with people involved in accidents built in the project Social and Economic Impacts of the Traffic Accidents in Brazilian Highways and the database of traffic accidents from the Federal Road Policy (Datatran). The analysis of the data was useful as pilot project, but not enough to establish with statistical confidence which factors are aggravating to an accident or to point out priorities for public policies to the reduction of the morbimortality of accidents. To this intent, a specific study was recommended, focusing on the severity of injuries and factors associated to it, as well as a complementary research with data from autopsies, in order to evaluate, among others, if some deaths could have been prevented by proper pre-hospital care.
Keywords: R41; 330; Straßenverkehrsunfall; Gesundheitskosten; Brasilien